A Clinical and Miasmatic Study of Cervical Spondylosis and its Homoeopathic Management- A Prospective Study (Advancements in Homeopathic Research, 2023)
Background & Objectives It is a degenerative disorder affecting the cervical  spine, where degeneration of the intervertebral disc  leads to changes in surrounding bones and ligaments,  gradually there is a formation of a bar-like structure  protruding at intervertebral areas. The fifth and sixth  cervical vertebrae are most commonly involved.  My study is to understand the effectiveness of the  Miasmatic approach of Homoeopathy in treating  cervical spondylosis and also to assess the severity of  neck pain which affects a patient’s daily life by using  the Neck Disability Index Scale.  Methods This Prospective experimental study which is  conducted at Vinayaka Missions Homoeopathic  Medical College and Hospital, Salem, during the  year 2015-2017. 30 patients were selected based on  Purposive sampling based on inclusion and exclusion  criteria. Neck Disability Index Score was taken as  an assessment scale in which all symptoms of the  patients were collected before and after the treatment.  After case taking the symptoms were analysed, and  evaluated and the totality of symptoms worked out  based on Dr J T Kent's Repertorization method  with consideration of Miasm present in each case.  Miasmatic analysis was done based on mental and  physical generals, Past history, presenting complaint  and family history of the patient. Paired t-test was  used to assess the improvement after the treatment  based on the score of the Neck disability index. X-ray  was taken before and after the treatment. Cervical  Radiculopathy and Myelopathy were diagnosed by  different clinical examinations. This study protocol  was approved by the Institutional Ethical Committee  of VMHMC & Hospital, Salem. Consent was  obtained from the patient and all the patients were  followed for 6-12 months.
Keywords: Clinical; Miasmatic Study; Cervical Spondylosis; Homoeopathic